Expression and purification of antigenic recombinant slmc 179 dengue-2 virus envelope protein in BL21-SI escherichia coli cells - De Guzman, Roche Rey Caballes (2003)
The pathogenic mosquito-borne dengue virus serotypes 1,2,3, and 4 are the causative agent of the pandemic dengue virus infection. Until now. there is no commercial vaccine to rotect the human population against these viruses. Several strategies have been attempted through the course pf dengue vaccine development. One of which is the use of recombinant subunits, specifically the Dengue envelope protein. Recombinant envelope subunit id promising since it is relatively simple and cost-effective to produce. Moreover, it has been shown to generate anti-dengue virusa neutralizing and protective antibodies.
Thesis (M.S. Molecular Biology & Biotechnology)--University of the Philippines Diliman.
Keywords: Dengue viruses; Dengue virus -- Vaccination -- Philippines -- Research